Repeatability of vessel density measurements of optical coherence tomography angiography in normal and glaucoma eyes. Issue 3 (24th July 2017) - Venugopal, Jayasree P; Rao, Harsha L; Weinreb, Robert N; Pradhan, Zia S; Dasari, Srilakshmi; Riyazuddin, Mohammed; Puttiah, Narenda K; Rao, Dhanraj A S; Devi, Sathi; Mansouri, Kaweh; Webers, Carroll AB
Abstract : Aims: To compare the intrasession repeatability of peripapillary and macular vessel density measurements of optical coherence tomography angiography (OCTA) in normal and glaucoma eyes, and to evaluate the effect of signal strength of OCTA scans on the repeatability. Methods: In a cross-sectional study, three optic nerve head scans each of 65 eyes (30 normal, 35 glaucoma eyes) and three macular scans each of 69 eyes (35 normal, 34 glaucoma eyes) acquired in the same session with OCTA were analysed. Repeatability was assessed using within-subject coefficient of repeatability (CRw) and variation (CVw). Effect of signal strength index (SSI) on repeatability was evaluated with repeated-measures mixed-effects models. Results: CRw (%) and CVw (%) of peripapillary measurements in normal eyes ranged between 3.3 and 7.0, and 2.5 and 4.4 respectively, and that in glaucoma eyes between 3.5 and 7.1, and 2.6 and 6.6. For the macular, these measurements ranged between 4.1 and 6.0, and 3.3 and 4.7 in normal eyes and 4.3 and 6.9, and 3.7 and 5.6 in glaucoma eyes. Repeatability estimates of most measurements were similar in normal and glaucoma eyes. Vessel densities of both peripapillary and macular regions significantly increased with increase in SSI of repeat scans (coefficients ranging from 0.15 to 0.38, p<0.01 for all associations). Conclusions: Repeatability estimates of OCTA measured peripapillary and macular vessel densities were similar in normal eyes and eyes with glaucoma. SSI values of the scans had a significant effect on the repeatability of OCTA with the vessel density values increasing in scans with higher SSI values.